Mating Responses in Candida lipolytica - Herman, A. I. (1971)
Culture medium that restricted cell multiplication increased fertility in selected heterothallic stocks of Candida lipolytica and triggered sporulation in newly formed diploids; a medium that supported vigorous cell growth prevented sporulation and permitted the newly formed diploids to bud.